2019
DOI: 10.1021/acs.jpclett.9b01369
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Anodic–Cathodic Nanocollision Events Reveal Redox Behaviors of Single Silver Nanoparticles

Abstract: We reported a novel method to real-time monitor the redox behaviors of single Ag nanoparticles (AgNPs) at a Au ultramicroelectrode between oxidizing and reducing pulse potentials using the nanocollision electrochemical method. At fast pulse potentials, the instantaneous anodic–cathodic current transients of a single AgNP were observed for the electrooxidation of AgNP, followed by the electroreduction of the newborn silver oxide (AgO) NP in alkaline media via switching of redox potentials; however, only anodic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 42 publications
4
16
1
Order By: Relevance
“…To further demonstrate the effect of adsorptive interactionmodulated electrochemical behavior, we attempted to investigate the strong coupling of the AgO x /Au system using stochastic collision measurements. Considering the formation of silver oxide in alkaline media [42][43][44][45][46][47] , we performed the electrochemical oxidation of 34 nm AgNP at an Au UME in a pH = 11.4 of an alkaline solution containing 15 mM PB and 10 mM NaOH (Fig. 2c).…”
Section: Resultsmentioning
confidence: 99%
“…To further demonstrate the effect of adsorptive interactionmodulated electrochemical behavior, we attempted to investigate the strong coupling of the AgO x /Au system using stochastic collision measurements. Considering the formation of silver oxide in alkaline media [42][43][44][45][46][47] , we performed the electrochemical oxidation of 34 nm AgNP at an Au UME in a pH = 11.4 of an alkaline solution containing 15 mM PB and 10 mM NaOH (Fig. 2c).…”
Section: Resultsmentioning
confidence: 99%
“…According to these standard reduction potentials, the production of nanoparticles of these metals, e.g., AuNPs and AgNPs, using common moderate reduction agents that do not have significantly high negative reduction standard potentials—e.g., hydrogen [ 94 , 95 , 96 ], carbon monoxide [ 97 , 98 ], citrate [ 95 , 99 , 100 , 101 ], hydroxylamine [ 95 ], formaldehyde [ 95 ], ascorbate [ 95 ], squartic acid [ 95 ], and BH 4 − [ 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 ]—cannot start with the simple reduction of the cations to atoms, as commonly assumed. Hafez et al [ 113 ] experimentally confirmed the absence of such cathodic reduction behaviors in a neutral system. The release of single hydrated aqueous atoms of silver or gold without any stabilizing agent by using H 2 (g), CO(g) or BH 4 − (aq), as in the above example, is thermodynamically impossible, as the potential of the cell becomes negative.…”
Section: Standard Reduction Potentialsmentioning
confidence: 99%
“…The transformation of AgNPs to Ag halides is usually observed at low pH values; the oxidation takes place in a single collision, for small AgNPs, or by consecutive collision events with typical single or multiple spikes features for larger particles [22–25,31] . In contrast, at higher pH, AgNPs were found to oxidize to AgO x concurrent with water oxidation and the associated current transients are characterized by an initial current spike followed by a tailing current region [32–34] . Additionally, Ag oxidation to sparingly soluble halides usually occurs in the presence of low halide concentrations, [35] while at high concentration of halides.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25]31] In contrast, at higher pH, AgNPs were found to oxidize to AgO x concurrent with water oxidation and the associated current transients are characterized by an initial current spike followed by a tailing current region. [32][33][34] Additionally, Ag oxidation to sparingly soluble halides usually occurs in the presence of low halide concentrations, [35] while at high concentration of halides. soluble silver halide complexes are formed.…”
Section: Introductionmentioning
confidence: 99%